TANGGUNG JAWAB PELAKU USAHA TERHADAP CACAT PRODUK PADA BAJU OBRAL DALAM TRANSAKSI ELEKTRONIK - Rizqi Eldar Putra, (2022)
This thesis discusses the legal protection for consumers due to the sale of defective products and the responsibility of business actors for consumer losses. In the consumer protection law as regulated in Law No. 8 of 1999 concerning Consumer Protection, Article 4 specifically states that one of the rights of consumers is to obtain goods that are appropriate and in accordance with those offered by business actors. However, many business actors justify any means to get big profits, including hidden defects in the clothes on sale. In fact, Article 11 of the UUPK has regulated the prohibition for business actors from selling goods on sale to hide and/or deceive consumers. In this case, the business actor is responsible for consumer losses due to product defects on sale clothes. This thesis uses a normative juridical research method with data collection methods in the form of library research. As an effort to prevent the sale of defective clothing items on sale, a clearer law is needed regarding the sale transaction system and how the provisions for sale transactions are made so that sales transactions are clearer. Even clearer regulations can be a preventive measure so that business actors do not carry out prohibited acts that harm consumers and can also be held responsible for their actions.